Characteristics of long‐chain acyl‐CoA synthetases in metabolism and cancer - Linlin Zhang; Xiangdong Wang (Wiley, 2023)
Abstract The deregulation of the metabolic network of cancer cells is now considered one of the characteristics of cancer. Aberrant lipid synthesis and additional lipid intake promote the rapid proliferation of cancer cells. In mammals, there are five members of the long‐chain acyl‐CoA synthase family involved in de novo lipid synthesis, fatty acid (FA) degradation and subsequent membrane modification. Their main function is to activate long‐chain FAs through the CoA chain link, and these conjugates are mainly used for the synthesis of triglycerides. In a variety of cancers, the expression of long‐chain acyl‐CoA synthetases (ACSLs) is different, and it also changes in different cancer subtypes. This review summarized recent research on the biological functions of ACSL, as well as recent advances in related diseases, and explored the potential therapeutic role of ACSL genes.